PRELIMINARY INVESTIGATION OF THE EFFECT OF DIFFERENT DOSES GNRH (GONADDOTROPIN RELEASING HORMON ) AND BOVINE LH (LISTERING HORMON) ON PLASMA LH AND TESTOSTERON CONCENTRATION IN MALE DOGS - Aris Junaidi; T.E. Trigg (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2002)
Six male adult dogs were randomized into 2 equal groups. Groups 1, dogs were